Effect of plant density, sowing date and fertilization on the sunflower agronomic characteristics. I. Grain yield and oil and yield components - de Almeida, Milton Luiz; da Silva, Paulo Regis Ferreira (Pesquisa Agropecuaria Brasileira, 1993)
With the objective of identifying possible interactions between plant density, planting date and soil fertility regarding grain yield and components, percentage and yield of oil, an experiment was conducted at Eldorado do Sul, RS, Brazil, during the 1988/89 growing season. Four planting densities (30,000, 45,000, 60,000 and 75,000 pl/ha) and two planting dates (July, 27 and September, 19) were tested with and without fertilizer application. In the first planting date, grain yield increased with the increase of plant density for 75,000 and 60,000 pl/ha respectively, for treatments with and without fertilizer. For the second planting date, plant density response was obtained only with fertilizer. The percentage of oil increased as plant density also did only for the first planting date. Oil yield showed a similar response to that of grain yield.
Keywords: Helianthus annuus; weight of 1; 000 seeds; number of seeds per head; density; planting date; soil fertility